Research of the Process of Dual Beam Laser Hardening of Small Module Rack - Mo Hengyang; Xiong Dahui; Yang Zhixiang; Ye Bing; Qi Xiaoyong (Jixie chuandong)
The laser hardening process is carried out on the tooth surface of 40 Cr rack with module of 2. 5 in high precision linear guide by utilizing a 3 k W diode laser. The single beam laser and dual beam laser hardening process are researched separately. The results show that,when using the single beam laser,the reflected energy have little effect on the microhardness of tooth surface,but the hardened surface will be tempered by the heat conducted from the other side. Compared with the single beam laser,the dual beam laser has many advantages such as lower laser power,more efficiency and more uniform distribution of microhardness.